2022
DOI: 10.1007/s10555-022-10030-w
|View full text |Cite
|
Sign up to set email alerts
|

Message in the bottle: regulation of the tumor microenvironment via exosome-driven proteolysis

Abstract: Exosomes comprise a subtype of extracellular vesicles involved in cell-to-cell communication, specifically by transporting biological molecules, such as proteins and nucleic acids, to either local or more distant recipient cells, thus triggering distinct biological behaviours. Included in the exosome cargo is frequently a wide range of proteolytic enzymes, such as the matrix metalloproteinases (MMPs), the disintegrin and metalloproteinases (ADAMs), and the ADAM with thrombospondin-like motifs (ADAMTSs), whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The extensive use of transmission electron microscopy (TEM) has confirmed that exosomes are extracellular vesicles (EVs) characterized by low electron density and a cupshaped morphology [36,37] in both the plasma and ascites of the OC patients (Figure 2). Additionally, cryo-electron microscopy has identified subpopulations of exosomes with single-, double-, and multi-layer membranes [36,38,39].…”
Section: Morphology and Content Of Exosomesmentioning
confidence: 99%
“…The extensive use of transmission electron microscopy (TEM) has confirmed that exosomes are extracellular vesicles (EVs) characterized by low electron density and a cupshaped morphology [36,37] in both the plasma and ascites of the OC patients (Figure 2). Additionally, cryo-electron microscopy has identified subpopulations of exosomes with single-, double-, and multi-layer membranes [36,38,39].…”
Section: Morphology and Content Of Exosomesmentioning
confidence: 99%
“…The Endosomal sorting complex required for transports (ESCRT) is involved in classical exosome formation. The ESCRT complex can be broadly divided into four components of ESCRT0, ESCRTTI, ESCRTII and ECRTIII (78)(79)(80). During the biogenesis of MVBs, the cellular material to be transported is ubiquitinated and the ESCRT0 complex is recruited to the membrane of the secretory endosome.…”
Section: Overview Of Exosomesmentioning
confidence: 99%
“…The function of matrix-metalloproteinases (MMPs) and A disintegrin and metalloproteinases (ADAMs) has been extensively characterised in tumorigenesis. Indeed, dysregulation of these proteases was found to promote tumour progression by supporting ECM remodelling, angiogenesis, cancer cell migration and invasion, and disruption of cancer-associated immune reactions [ 2 , 3 ] . Since these proteases have been found relevant to the progression of several types of cancer, they were considered as potential targets for cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%